Religion, Political Contestation and Democracy: Kiai's Role as Vote Broker in Madurese Local Political Battle - Asmawati Asmawati; Towar Ikbal Tawakkal; Sholih Muadi (Buletin Al-Turas, 2021)
This study aimed to know how the kiai as religious figures who had the highest social status in Pamekasan Regency carried out their work as vote brokers. This study was a qualitative research with a case study method. The research depended on verbal data and information of vote raising done by public figures in a Madurese local election. Intensive interview with some kiai as the key informants was done to get the intended information. They were chosen as primary data sources because they were public religious figures whom the people adhere to. The result showed that kiai with their social capital as vote brokers mobilizing the masses properly attracted political bosses who competed in the local election. Kiai with their religiosity played as an intermediary in delivering material for intended voters. However, it was unethical when the kiai as a religious figure provided material for voters. As a local figure who has a good image in a community, kiai became a major element in the progress of the democratic process. It can be concluded that the kiai as a highly respected religious figure contributed to the democracy to be well organized in the future.